Risk and contract management practices, and construction projects performance: A test of moderation by managerial skills - Waithaka Huria Karugu; Kirema Nkanata Mburugu; Duncan Mugambi Njeru (PLoS ONE, 2026)
Kenya’s socioeconomic development is heavily dependent on the construction industry; however, poor risk and contract management typically results in cost overruns, delays, and quality deficiencies that undermine project performance. Therefore, this study examined the way risk management practices affect the performance of building projects in the Nairobi Metropolitan Area, considering contract management practices and the moderating effect of project managers’ skills. The Theory of Constraints and Agency Theory, which place a strong emphasis on supervision, responsibility, and the removal of performance barriers, serve as the foundation for the analysis. The study used a descriptive and explanatory research design. 127 completed construction projects (95 residential and 32 non-residential) comprised the target population for this study. From this, 64 valid responses (96% response rate) were obtained from a sample of 67 projects chosen by stratified random sampling using Slovin’s technique at a 95% confidence level. A standardized Likert-scale questionnaire was used to collect data. Inferential statistics, such as simple linear and hierarchical multiple regressions and Pearson’s correlation analysis, were utilized to evaluate relationships and prediction effects. Descriptive statistics, such as means, percentages, and standard deviations, were utilized to define the project’s characteristics. Expert review was used to guarantee the validity of the instrument, and reliability was verified using Cronbach’s alpha coefficients greater than 0.70. The results demonstrate that both risk management practices (β = 0.612, p < 0.001) and contract management practices (β = 0.239, p = 0.020) are significant positive predictors of construction project performance, with the combined model accounting for 60.6% of the variance in construction project outcomes (R² = 0.606). Project manager skills did not significantly moderate the relationship between these management practices and project performance (interaction terms p > 0.05) and exhibited no significant independent effect (β = 0.132, p = 0.120), contributing only a marginal increase in explanatory power to R² = 0.62. The study concludes that while robust risk and contract management frameworks are critical for project success, the additive value of project manager skills remains modest and non-moderative. Recommendations include establishing uniform industry protocols and continued emphasis on professional certification and leadership development to support, rather than substitute systemic management practices.